Study on prevalence and surgical management of haemorrhoids in a tertiary care teaching hospital in a rural area - Farook, A.; Periasamy, A.; Arvind, S.; Kannan, I. (International Surgery Journal, 2018)
Background: Haemorrhoids, which is also termed as piles characterized by the enlarged and bulged blood vessels surrounding the supporting tissues present in the anal canal of an individual. In the present study, an attempt has been made to find the prevalence of haemorrhoids and surgical management done in our geographical area. Methods: The present study was retrospective, cross-sectional study from the period of 1st January 2013 to 31st December 2017. A total of 351 haemorrhoids patients were admitted in inpatient surgical ward during that period. The demographic details of all the patients were noted from the medical records. Results: 219 (62%) patients were male and 132 (38%) were females. Most of the patients are predominantly adults above the age of 21 years. The post-operative stay in hospital is almost less than 10 days as it indicates that most of the patients were discharged without any complication. Conclusions: The male patients are predominant compared to female patients. The surgical complications are less. The exact prevalence rate may be high as some patients may either undergo a self-treatment or native medicine treatment.